Membangun Brand Awareness Melalui Strategi Konten di Media Sosial Adi and Friends Wedding Organizer - Kennixson; Nigar Pandrianto (Kiwari, 2025)
This study draws on New Media Theory, which highlights the role of digital technology in shaping new patterns of communication, and Social Media Theory, which emphasizes the importance of two-way interaction in building relationships with audiences. The high-quality visual content strategy implemented by Adi & Friends Wedding Organizer aligns with Brand Awareness Theory, as such content effectively enhances brand visibility and recognition. Active engagement through comments and direct messages reflects the role of audience interaction in strengthening emotional bonds and building trust. Additionally, the use of customer testimonials aligns with Viral Theory, as authentic customer experiences can broaden audience reach and reinforce brand credibility. These strategies demonstrate that social media functions not only as a promotional tool but also as a platform for building long-term, sustainable relationships with audiences. The findings affirm the practical application of these theories in optimizing brand awareness through social media strategies. Penelitian ini merujuk pada Teori Media Baru yang menyoroti peran teknologi digital dalam membentuk pola komunikasi yang baru, serta Teori Media Sosial yang menekankan pentingnya interaksi dua arah dalam membangun hubungan dengan audiens. Strategi konten visual berkualitas tinggi yang diterapkan oleh Adi & Friends Wedding Organizer sejalan dengan Teori Kesadaran Merek (Brand Awareness), karena mampu meningkatkan visibilitas dan pengenalan merek secara efektif. Keterlibatan aktif melalui komentar dan pesan langsung mencerminkan peran interaksi audiens dalam memperkuat ikatan emosional dan membangun kepercayaan. Selain itu, penggunaan testimoni pelanggan selaras dengan Teori Viralitas, karena pengalaman autentik dari pelanggan dapat memperluas jangkauan audiens dan memperkuat kredibilitas merek. Strategi ini menunjukkan bahwa media sosial tidak hanya berfungsi sebagai alat promosi, tetapi juga sebagai platform untuk membangun hubungan jangka panjang yang berkelanjutan dengan audiens. Temuan ini menegaskan penerapan teori-teori tersebut dalam strategi media sosial guna mengoptimalkan kesadaran merek.